Life at four corners : religion, gender, and education in a German-Lutheran community, 1868-1945 - Coburn, Carol (Rural America (Lawrence, Kan.), 1992)
Defined less by geography than by demographic character, Block, Kansas, in many ways exemplifies the prevalent yet seldom-scrutinized ethnic, religion-based community of the rural Midwest. Physically small, the town sprang up around four corners formed by crossroads. Spiritually strong and cohesive, it became the educational and cultural center for generations of German-Lutheran families. In this book Carol Coburn analyzes the powerful combination of those ethnic and religious institutions that effectively resisted assimilation for nearly 80 years only to succumb to the influences of the outside world during the 1930s and 1940s. Emphasizing the formal and informal education provided by the church, school, and family, she examines the total process of how values, identities, and all aspects of culture were transmitted from generation to generation.